Anticancer Activity of Garcinia morella on T-Cell Murine Lymphoma Via Apoptotic Induction - Choudhury, Bhaswati; Kandimalla, Raghuram; Bharali, Rupjyoti; Monisha, Javadi; Kunnumakara, Ajaikumar B.; Kalita, Kasturi; Kotoky, Jibon (Frontiers in Pharmacology, 2016)
Traditional knowledge (TK) based medicines have gained worldwide attention and presently the scientific community is focussing on proper pharmacological validation and identification of lead compounds for the treatment of various diseases. The North East region of India is the home of valuable traditional herbal remedies. Garcinia morella Desr. (Guttiferae) is one such medicinal plant used by traditional healers for the treatment of inflammatory disorders. The present study was aimed to evaluate the antioxidant and anticancer activity of methanol extracts of the leaf, bark and fruit of G. morella (GM) in different in vitro and in vivo experimental conditions. The results of this study showed that GM methanol extracts possessed in vitro antioxidant and anticancer properties, where the fruit extract (GF) showed maximum activity. The anticancer activity was further confirmed by the results of in vivo administration of GF (200 mg/kg) for ten days to Dalton’s lymphoma (DLA) induced mice. GF extract significantly increased the mean survival time (MST) of the animals, decreased the tumor volume and restored the hematological and biochemical parameters. The present study for the first time reported the anticancer property of GF on DLA. Further from the experiments conducted to elucidate the mechanism of action of GF on DLA, it can be concluded that GF exerts its anticancer effect through induction of caspases and DNA fragmentation that ultimately leads to apoptosis. However, further experimentation is required to elucidate the active principle and validate these findings in various in vivo settings.